WEWENANG OTORITAS JASA KEUANGAN (OJK) TERHADAP PENYELESAIAN SENGKETA PASAR MODAL OLEH BADAN ARBITRASE PASAR MODAL INDONESIA (BAPMI) - Adha, Syaichul; Sri Indrawati, A. A. (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
The title of this journal reads “The Authority of Indonesia Financial Service Authority (OJK) Towards Capital Market Alternative Dispute Resolution, Conducted by Indonesian Capital Market Arbitration Board (BAPMI)”. This writing method uses the normative legal method through statute approach. From the legal writing conclusions below there were found two authority of OJK towards BAPMI. The first authority is capital market consumer and the people protection and the second is receives notification if there is party in dispute that is not performing according to BAPMI Arbitration Decision.
Keywords: Authority, Indonesia Financial Services Authority (OJK), Alternatif Dispute Resolution (ADR), and Indonesian Capital Market Arbitration Board (BAPMI)